Tinggalan Arkeologi Di Pura Penataran Kacang Bubuan Mas - Irfan, Mochamad; Srijaya, I Wayan; Palupi Titasari, Coleta (Humanis; Vol 23 No 4 (2019)DO - 10.24843/JH.2019.v23.i04.p06, 2019)
In Bali, the archaeological remains is still functioned and sanctified by the public by placing them in a temple, one of them is Penataran Kacang Bubuan Mas Temple, Ubud, Gianyar regency. The methodin this study is a qualitative committee method which will produce desktiptif data in the form of written words. Data analyis being applied in this research is the qualitative analysis,iconography analysis and contextual analysis. Some theories being applied in this research is the functional theory and semiotics theory. Based on the analysis, the conclusions are drawn in the form of archaeological heritage of 1 piece Ganesha statue,1 piece simpel statue (primitive statue), 6 pieces embodiment statues of bhatari, 2 pieces embodiment statues of bhatara, 1 piece lingga (tribhaga), 2 pieces animal statues, 1 piece priest statue, 1 pieces clownman statue, 4 pieces fragments of statues, 1 piece fragment waterless building fragment, 1 piece natural stone. Archaelogical remains in Penataran Kacang Bubuan Mas Temple, Ubud, Gianyar regency when viewed from its function in the past has experienced a shift function. The local community is still sanctify archaeological remains as a workship tool to ask for safety and protection from harm and fertility . The meaning of the archaeological remains found in the temple is sacred objects for the means of worship by the penyungsung pura community. The means of worshiping the requested statues is symbolism or symbolic that connects worshipers with gods, ancestral holy spirits or for Sang Hyang Widhi Wasa (God).